Design and Modeling of a Bio-Inspired Flexible Joint Actuator - Ming Xu; Cheng Rong; Long He (Actuators, 2021)
Spiders rely on a hydraulic system to stretch their legs but use muscles to make their legs flex. The compound drive of hydraulics and muscle makes an integrate dexterous structure with powerful locomotion abilities, which perfectly meets the primary requirements of advanced robots. Inspired by this hydraulics-muscle co-drive joint, a novel flexible joint actuator was proposed and its driving characteristics were preliminarily explored. The bio-inspired flexible joint manifested as a double-constrained balloon actuator, which was fabricated by the composite process of 3D printing and casting. To evaluate its performance, the mathematical model was deduced, as well as the finite element analysis (FEA) model. A series of experiments on the rotation angles, driving forces, and efficiencies of the flexible joint were carried out and compared with the mathematical calculations and FEA simulations. The results show that the accuracy of the two theoretical models can be used to assess the joint actuator. The locomotion test of a soft arthropod robot with two flexible joints was also implemented, where the moving speed reached 22 mm/s and the feasibility of the proposed flexible joint applied to a soft robot was demonstrated.